Games + activities + projects : bringing math home : a parent's guide to elementary school math - Churchman, Suzanne L. (Zephyr Press, 2006)
This ultimate parents' guide to elementary school math features projects, games, and activities children and parents can do together to increase their understanding of basic math concepts.